Markers of pancreatic cancer: Working towards early detection - Goggins, Michael (2011)
Because early detection of pancreatic cancer is the best way to cure this disease, investigators continue to try and identify accurate markers of early pancreatic cancer. Since early-stage pancreatic cancer is generally asymptomatic, the only reliable way to detect it is by targeting individuals at increased risk for pancreatic screening.